Analisis Kebijakan Sertifikasi Guru dalam Meningkatkan Profesionalitas Guru pada Satuan Pendidikan - Fitri Ayu Ilahana; Sri Minarti (CV. ITTC INDONESIA, 2026)
This study aims to analyze teacher certification policies in improving teacher professionalism at educational institutions, particularly at SMKN Ngambon. The research employed a qualitative approach with a descriptive research design. Data were collected through interviews, observations, and documentation involving a certified Computer and Network Engineering teacher as the research subject. The findings indicate that teacher certification has a positive influence on improving teacher professionalism, especially in terms of discipline, responsibility, instructional innovation, and the ability to adapt to educational technology developments. Teacher certification also enhances teachers’ work motivation through professional allowances as a form of government appreciation for the teaching profession. However, the implementation of certification policies still faces several challenges, including heavy administrative workloads and additional responsibilities that may reduce the effectiveness of the teaching and learning process. Therefore, teacher certification policies should be supported by continuous professional development programs to improve the overall quality of education effectively.